Flour from Prosopis alba cotyledons: A natural source of nutrient and bioactive phytochemicals - Cattaneo, Florencia (2016)
The Prosopis alba seed is a waste material in the process to produce pod flour. To suggest a potential use of these seeds it is necessary to determine the nutritional, phytochemical and functional quality of cotyledon flour from Prosopis alba. This flour showed high level of proteins (62%), low content of total carbohydrate and fat. Free polyphenol (1150 ± 20 mg GAE/100 g flour) and carotenoids (10.55 ± 0.05 mg β-CE/100 g flour) compounds were the dominant compounds. The main identified constituents in the polyphenolic extracts were C- glycosyl flavones, including schaftoside, isoschaftoside, vicenin II, vitexin and isovitexin. The extract enriched in polyphenolic compounds exhibited ABTS+ reducing capacity and scavenging activity of H2O2; and was able to inhibit phospholipase, lipoxygenase and cyclooxygenase, three pro-inflammatory enzymes. According to our results, the P. alba cotyledon flour could be considered as a new alternative in the formulation of functional foods or food supplements.